Ion channels and pain in Fabry disease - Weissmann, Carina (2021)
Fabry disease (FD) is a progressive, X-linked inherited disorder of glycosphingolipid metabolism due to deficient or absent lysosomal α-galactosidase A (α-Gal A) activity which results in progressive accumulation of globotriaosylceramide (Gb3) and related metabolites. One prominent feature of Fabry disease is neuropathic pain. Accumulation of Gb3 has been documented in dorsal root ganglia (DRG) as well as other neurons, and has lately been associated with the mechanism of pain though the pathophysiology is still unclear. Small fiber (SF) neuropathy in FD differs from other entities in several aspects related to the perception of pain, alteration of fibers as well as drug therapies used in the practice with patients, with therapies far from satisfying. In order to develop better treatments, more information on the underlying mechanisms of pain is needed. Research in neuropathy has gained momentum from the development of preclinical models where different aspects of pain can be modelled and further analyzed. This review aims at describing the different in vitro and FD animal models that have been used so far, as well as some of the insights gained from their use. We focus especially in recent findings associated with ion channel alterations -that apart from the vascular alterations-, could provide targets for improved therapies in pain.